A zirconium-based MOF adsorbent and its preparation method and application

By preparing zirconium-based MOF adsorbent, using its electrostatic and coordination effects, the problems of poor effect and poor reversibility of existing adsorbents when removing copper ions in water bodies are solved, and efficient and reversible copper ion adsorption effect is achieved.

CN116178741BActive Publication Date: 2025-04-22KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310190145.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-02
Publication Date
2025-04-22
Estimated Expiration
2043-03-02

AI Technical Summary

Technical Problem

When removing copper ions in water, existing adsorbents have problems such as poor adsorption effect, may cause secondary pollution, difficult recycling and regeneration, and poor reusability.

Method used

A zirconium MOF adsorbent is used, which is prepared by combining 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane to form the organic ligand DKTA and combined with ZrCl4. This adsorbent has efficient copper ion adsorption ability through electrostatic and coordination effects.

Benefits of technology

Zirconium-based MOF adsorbent can achieve a copper ion adsorption rate of 99.84%, and still maintains an adsorption efficiency of 91.65% after repeated use, and has good reversibility and regeneration ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004105129230000021
    Figure BDA0004105129230000021
  • Figure BDA0004105129230000022
    Figure BDA0004105129230000022
Patent Text Reader

Abstract

The present invention relates to a zirconium-based MOF adsorbent and a preparation method and application thereof, and belongs to the technical field of composite materials. The present invention utilizes an organic ligand DKTA generated by the reaction of 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane (DBM), and combines the organic ligand DKTA with ZrCl4 to prepare a zirconium-based MOF adsorbent; the zirconium-based MOF adsorbent can be used for targeted removal of copper ions in a solution; the adsorption rate of the zirconium-based MOF adsorbent on copper ions can reach 99.84%, and after repeating 5 times, the adsorption rate of copper ions can also reach 91.65%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a zirconium-based MOF adsorbent and a preparation method and application thereof, belonging to the technical field of composite materials. Background Art

[0002] Heavy metal water pollution refers to the abnormal concentration of metal elements and their compounds with a relative density of more than 4.5 in water, which causes the water quality to deteriorate or worsen. Copper (Cu(II)) is an important trace metal. Its trace content (0.03-0.06 mg / d) is non-toxic, but if copper exceeds the standard in the human body, the harm to health is enriched, hidden, and irreversible. By destroying the binding of enzymes and proteins to the body, it puts a burden on human organs, especially the liver and gallbladder, and even causes life-threatening consequences. Copper mining, smelting, electroplating and electronics industries discharge a large amount of copper-containing wastewater every year. The discharge of heavy metal copper ions is extremely harmful to water bodies and soil. Therefore, Cu(II) in wastewater must be limited to a certain range to avoid harming human health and soil and food safety.

[0003] In recent years, the removal of copper ions has been achieved by using technologies such as photocatalysis, biological treatment and electrochemical degradation. Although the technologies are relatively complete, some technologies still have some disadvantages, mainly manifested in high energy consumption, difficult technical requirements and high costs. In terms of material development, a large number of new materials are used to remove various types of pollutants by changing the physicochemical properties of pollutants. Especially important is the development of improved materials for metal ions or heavy metal ions. When it comes to targeted removal of Cu(II) in water, material adsorption / capture is the most effective method.

[0004] Graphene, activated carbon, gels and metal organic framework materials are examples of common adsorbents. However, with current production technology, it is very difficult to achieve commercial production of graphene materials. In addition, some toxic properties and impurities are still retained in the graphene during the production process; powdered activated carbon has a better adsorption effect than granular carbon, but the resulting dust problem limits large-scale application; and saturated activated carbon is complex to handle, has low adsorption capacity, and poor mechanical strength, which makes it difficult to recycle and regenerate, and poor reusability limits the adsorption of Cu(II) in water by gel. Summary of the invention

[0005] In view of the problems of poor adsorption effect, possible secondary pollution, great difficulty in recycling and regeneration, and poor reusability, the present invention proposes a zirconium-based MOF adsorbent and a preparation method and application thereof. 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane are used to generate an organic ligand DKTA, and the organic ligand DKTA is combined with ZrCl4 to prepare the zirconium-based MOF adsorbent; the zirconium-based MOF adsorbent can be used for targeted removal of copper ions in a solution.

[0006] A zirconium-based MOF adsorbent is prepared by using 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane to generate an organic ligand DKTA, and the organic ligand DKTA is combined with ZrCl4 to obtain a zirconium-based MOF adsorbent, and the structural formula is:

[0007]

[0008] The preparation method of zirconium-based MOF adsorbent, the specific steps are as follows:

[0009] (1) 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane are added to anhydrous ethanol solvent, stirred and dissolved to obtain solution A, acetic acid is added to solution A, and then refluxed at a temperature of 77 to 83° C. for 7 to 9 hours, cooled to room temperature, separated from the solid and the liquid, and the solid is dried to obtain the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid, denoted as DKTA; the reaction formula is:

[0010]

[0011] (2) The ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid (DKTA) and ZrCl4 were ultrasonically dissolved in N,N-dimethylformamide, concentrated hydrochloric acid was added, and refluxed at a temperature of 127-133°C for 47-49 hours, cooled to room temperature, and the solid-liquid separation was performed. The solid was washed and soaked with N,N-dimethylformamide and anhydrous ethanol, and vacuum dried to obtain the zirconium-based MOF adsorbent DKTA-MOF; the reaction formula is:

[0012]

[0013] In the step (1), the molar ratio of 3-aminopyrazine-2-carboxylic acid to dibenzoylmethane is 1:0.4-0.6.

[0014] The mass concentration of 2,5-diaminobenzene-1,4-dithiol dihydrochloride in solution A of step (1) is 1.6-1.8 g / mL.

[0015] The molar concentration of 3-aminopyrazine-2-carboxylic acid in solution A of step (1) is 0.002-0.003 mol / mL.

[0016] In the step (1), the volume ratio of acetic acid to solution A is 1.5-2.5:100.

[0017] In the step (2), the mass ratio of the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid (DKTA) and ZrCl4 is 1:0.9-1.1.

[0018] The concentration of concentrated hydrochloric acid in step (2) is 36-38 wt %, the solid-liquid ratio g:mL of the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid (DKTA) and concentrated hydrochloric acid is 1.1:0.5-0.6, and the volume ratio of N,N-dimethylformamide to concentrated hydrochloric acid is 100:1.2-1.45.

[0019] The zirconium-based MOF adsorbent is used for targeted adsorption of copper ions in a solution.

[0020] The overall synthetic route of zirconium-based MOF adsorbents is

[0021]

[0022] Mechanism of the selective and efficient adsorption of copper ions by modified zirconium-based MOF adsorbents: MOF consists of one-dimensional, two-dimensional or three-dimensional structures composed of metal atoms or atomic clusters coordinated by organic ligands. By selecting suitable ligands and metal ion clusters to adjust the pore size and change the functional groups, DKTA-MOF with the extraordinary ability to remove aqueous Cu(II) ions was prepared; electrostatic and coordination effects play a dominant role in the adsorption of Cu(II) by DKTA-MOF. The non-uniform pores distributed in DKTA-MOF enrich the surface active sites and enhance the surface adsorption capacity for Cu(II); the adsorbent is negatively charged, and Cu(II) exists in the form of cations over the entire pH range, and the removal effect is achieved through electrostatic interactions; the nitrogen-containing functional groups form a more powerful coordination chelate with copper Cu(II) to remove Cu(II) from water.

[0023] The beneficial effects of the present invention are:

[0024] (1) The present invention utilizes 3-aminopyrazine-2-carboxylic acid and dibenzoyl to generate an organic ligand DKTA, and the organic ligand DKTA is combined with ZrCl4 to prepare a zirconium-based MOF adsorbent; the zirconium-based MOF adsorbent can target and remove Cu(II) from coexisting ions;

[0025] (2) The zirconium-based MOF adsorbent of the present invention utilizes organic matter with abundant adsorption sites to prepare amorphous metal skeleton adsorbents, showing excellent selectivity, design / operation flexibility and good reversibility;

[0026] (3) The adsorption rate of copper ions by the zirconium-based MOF adsorbent of the present invention can reach 99.84%. After repeating 5 times, the adsorption rate of copper ions can also reach 91.65%. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the SEM image of the zirconium-based MOF adsorbent of Example 1;

[0028] Figure 2This is the EDS image of the zirconium-based MOF adsorbent of Example 1;

[0029] Figure 3 is the XRD pattern of the zirconium-based MOF adsorbent of Example 1;

[0030] Figure 4 This is the XPS graph of the zirconium-based MOF adsorbent of Example 1;

[0031] Figure 5 FT-IR image of the zirconium-based MOF adsorbent of Example 1;

[0032] Figure 6 This is the SEM image of the zirconium-based MOF adsorbent after adsorbing copper ions in Example 1.

[0033] Figure 7 This is the EDS graph of the zirconium-based MOF adsorbent after adsorbing copper ions in Example 1;

[0034] Figure 8 This is an XPS comparison chart of the zirconium-based MOF adsorbent after adsorbing copper ions in Example 1;

[0035] Fig. 9 This is a FT-IR comparison chart of the zirconium-based MOF adsorbent in Example 1 and after adsorbing copper ions. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0037] Example 1: Preparation method of zirconium-based MOF adsorbent, the specific steps are as follows:

[0038] (1) 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane are added to 100 mL of anhydrous ethanol solvent, stirred and dissolved to obtain solution A, 2 mL of acetic acid is added to solution A, solution A is refluxed at 80° C. for 8 h, cooled to room temperature, solid-liquid separation is performed, the solid is washed with anhydrous ethanol and then vacuum dried for 12 h to obtain the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid (DKTA); wherein the molar ratio of 3-aminopyrazine-2-carboxylic acid to dibenzoylmethane is 1:0.5, and the molar concentration of 3-aminopyrazine-2-carboxylic acid in solution A is 0.0025 g / mL; the reaction equation is as follows:

[0039]

[0040] (2) The ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid (DKTA) and ZrCl4 were added to 100 mL of N,N-dimethylformamide and ultrasonically dissolved, and then 2 mL of concentrated hydrochloric acid was added. The mixture was refluxed at 130°C for 48 h, cooled to room temperature, and the solid-liquid separation was performed. The solid was washed with N,N-dimethylformamide and anhydrous ethanol for multiple times to remove unreacted substances, and then vacuum dried at 100°C for 12 h to obtain the MOF adsorbent DKTA-MOF; wherein the mass ratio of the ligand DKTA to ZrCl4 was 1:1, the solid-liquid ratio of the ligand DKTA to concentrated hydrochloric acid was 1:0.55 g:mL, and the volume ratio of N,N-dimethylformamide to concentrated hydrochloric acid was 100:1.33; the reaction equation is as follows:

[0041]

[0042] The SEM, EDS, XRD, FT-IR and XPS images of the zirconium-based MOF adsorbent of this example are shown in Figures 1 to 5 The zirconium-based MOF adsorbent is a block solid with a rough surface, uneven structure and an average particle size of about 200nm. It is mainly composed of elements C, N, O and Zr, with the weight percentages of C, N, O and Zr being 49.32%, 20.13%, 22.29% and 8.26% respectively; the characteristic peak of Zr also appears in the EDS graph; the XRD graph shows that only one Zr diffraction peak appears at 6.9°, indicating that the adsorbent has defects; FT-IR results show that 3435 and 3276cm -1 The peak corresponding to OH stretching vibration, 1375 cm -1 Corresponding to CN stretching vibration; at the same time, at 1445 and 1665cm -1 The peaks at are caused by the symmetric and asymmetric stretching of the O=CO of the carboxyl group, which also proves that the carboxyl group is closely related to Zr 4+ In addition, at 836cm -1 The vibration peak at 534 cm-1 can be assigned to the piperazine ring bending vibration peak. -1 The peaks at 1020 and 925 cm -1 The peak bands of piperazine correspond well, and the Zr-O bonds appear at 616 and 701 cm -1 At; preliminary conclusion of Zr 4+ Covered by carboxyl functional groups; XPS analysis showed peaks of Zr 3d, C 1s, O 1s and N1s at 182.20, 284.81, 398.73 and 530.74 eV; the above characterization results showed that the zirconium-based MOF adsorbent was successfully prepared;

[0043] Determination of the performance of adsorption of copper ions:

[0044] DKTA-MOF (10 mg) was added to a 15 mL centrifuge tube containing Cu(II) (pH 5, 10 mL, 100 mg / L) at room temperature, and the tube was shaken at 200 rpm for 20 h. The adsorbent was separated by centrifugation and the supernatant was obtained.

[0045] The adsorbed materials after adsorption of copper ions were analyzed by SEM, EDS, XPS and FT-IR (see Figure 6-9 ),Depend on Figure 6 and Figure 7 It can be obtained that after the adsorption of Cu(II), a certain amount of particulate matter was attached to the surface of DKTA-MOF, and a sharp peak of Cu(II) appeared in the EDS spectrum, and the Cu(II) content was 7.49%; Figure 8 (XPS) also found the characteristic peak of Cu; the peak value of Cu after adsorption was 942.35eV; Fig. 9 (FT-IR) found that after Cu(II) was adsorbed on the DKTA-MOF surface, the -1 The peak at 3433 cm -1 ), and tends to be broad, indicating that intermolecular hydrogen bonds play a role in the adsorption of Cu(II); in the DKTA-MOF spectrum of Cu(II) adsorption, the peak wavenumber (1375~1378cm -1 ) is due to the adsorption of Cu(II) on the CN groups; in addition, a peak from the low peak (1020 cm -1 ) to the peak (1028cm -1 ) and a significant increase in band intensity, demonstrating the importance of the piperazine ring in the formation of the covalent bond between Cu(II) and DKTA-MOF adsorbent; Taking all the above results into consideration, it is demonstrated that Cu(II) was successfully adsorbed by DKTA-MOF;

[0046] ICP-AES was used to determine the copper ion concentration in the supernatant of the centrifuge tube containing Cu(II). The copper ion adsorption rate was detected and calculated to be 99.84%. The adsorbent was eluted with a desorption solution (40 mL) composed of 1% concentrated hydrochloric acid and 10% thiourea for 20 hours, and the copper ion release rate was 98.87%. After centrifugation, the adsorbent was washed with distilled water until the solution was neutral to complete the regeneration of the adsorbent DKTA-MOF. After 5 repeated experiments, the copper ion adsorption rate for the fifth time was 93.91%, and the copper ion release rate was 92.43%.

[0047] Example 2: Preparation method of zirconium-based MOF adsorbent, the specific steps are as follows:

[0048] (1) adding 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane to 100 mL of anhydrous ethanol solvent, stirring and dissolving to obtain solution A, adding 1.8 mL of acetic acid to solution A, reflux reaction of solution A at 77° C. for 9 h, cooling to room temperature, solid-liquid separation, washing the solid with anhydrous ethanol and vacuum drying for 12 h to obtain the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid (DKTA); wherein the molar ratio of 3-aminopyrazine-2-carboxylic acid to dibenzoylmethane is 1:0.4, and the molar concentration of 3-aminopyrazine-2-carboxylic acid in the solution is 0.003 g / mL;

[0049] (2) Adding the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid (DKTA) and ZrCl4 to 100 mL of N,N-dimethylformamide, dissolving by ultrasound, adding 1.8 mL of concentrated hydrochloric acid, reacting under reflux at 127°C for 49 h, cooling to room temperature, separating the solid from the liquid, washing the solid with N,N-dimethylformamide and anhydrous ethanol for multiple times to remove unreacted substances, and vacuum drying at 100°C for 12 h to obtain the MOF adsorbent DKTA-MOF; wherein the mass ratio of the ligand DKTA to ZrCl4 is 1:0.9, the solid-liquid ratio of the ligand DKTA to concentrated hydrochloric acid is g:mL 1:0.5, and the volume ratio of N,N-dimethylformamide to concentrated hydrochloric acid is 100:1.2;

[0050] Determination of the performance of adsorption of copper ions:

[0051] DKTA-MOF (10 mg) was added to 15 mL centrifuge tubes containing Cu(II) (pH 5, 10 mL, 100 mg / L) at room temperature and oscillated at 200 rpm for 20 h on an oscillator; the adsorbent was separated by centrifugation and the supernatant was obtained; the copper ion concentration in the supernatant in the centrifuge tube containing Cu(II) was determined by ICP-AES, and the adsorption rate of copper ions was 99.24% through detection and calculation. The adsorbent was eluted with a desorption solution (40 mL) composed of 1% concentrated hydrochloric acid and 10% thiourea for 20 h, and the copper ion release rate was 98.53%; after centrifugation, the adsorbent was washed with distilled water until the solution was neutral to complete the regeneration of the adsorbent DKTA-MOF; after 5 repeated experiments, the adsorption rate of copper ions in the fifth time was 92.45%, and the copper ion release rate was 91.37%.

[0052] Example 3: Preparation method of zirconium-based MOF adsorbent, the specific steps are as follows:

[0053] (1) adding 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane to 100 mL of anhydrous ethanol solvent, stirring and dissolving to obtain solution A, adding 2.2 mL of acetic acid to solution A, reflux reaction of solution A at 83° C. for 7 h, cooling to room temperature, solid-liquid separation, washing the solid with anhydrous ethanol and vacuum drying for 12 h to obtain the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid (DKTA); wherein the molar ratio of 3-aminopyrazine-2-carboxylic acid to dibenzoylmethane is 1:0.6, and the molar concentration of 3-aminopyrazine-2-carboxylic acid in the solution is 0.002 g / mL;

[0054] (2) Adding the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid (DKTA) and ZrCl4 to 100 mL of N,N-dimethylformamide, dissolving by ultrasonication, adding 4.2 mL of concentrated hydrochloric acid, reacting under reflux at 133°C for 47 h, cooling to room temperature, separating the solid from the liquid, washing the solid with N,N-dimethylformamide and anhydrous ethanol for multiple times to remove unreacted substances, and vacuum drying at 100°C for 12 h to obtain the MOF adsorbent DKTA-MOF; wherein the mass ratio of the ligand DKTA to ZrCl4 is 1:1, the solid-liquid ratio of the ligand DKTA to concentrated hydrochloric acid is g:mL 1:0.6, and the volume ratio of N,N-dimethylformamide to concentrated hydrochloric acid is 100:1.5;

[0055] Determination of the performance of adsorption of copper ions:

[0056] DKTA-MOF (10 mg) was added to 15 mL centrifuge tubes containing Cu(II) (pH 5, 10 mL, 100 mg / L) at room temperature and oscillated at 200 rpm for 20 h on an oscillator; the adsorbent was separated by centrifugation and the supernatant was obtained; the copper ion concentration in the supernatant in the centrifuge tube containing Cu(II) was determined by ICP-AES, and the adsorption rate of copper ions was 99.59% through detection and calculation. The adsorbent was eluted with a desorption solution (40 mL) composed of 1% concentrated hydrochloric acid and 10% thiourea for 20 h, and the copper ion release rate was 98.93%; after centrifugation, the adsorbent was washed with distilled water until the solution was neutral to complete the regeneration of the adsorbent DKTA-MOF; after 5 repeated experiments, the adsorption rate of copper ions in the fifth time was 93.29%, and the copper ion release rate was 92.13%.

[0057] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A zirconium-based MOF adsorbent, characterized in that: Its structural formula is: ; The preparation method of the zirconium-based MOF adsorbent comprises the following specific steps: (1) 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane are added to anhydrous ethanol solvent, stirred and dissolved to obtain solution A, acetic acid is added to solution A, and then refluxed at a temperature of 77-83°C for 7-9 hours, cooled to room temperature, separated from the solid and the liquid, and the solid is dried to obtain the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid, denoted as DKTA; (2) The ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid DKTA and ZrCl4 Ultrasonic dissolution in N,N-dimethylformamide, adding concentrated hydrochloric acid, reflux reaction at 127-133 °C for 47-49 h, cooling to room temperature, solid-liquid separation, solid washing and soaking with N,N-dimethylformamide and anhydrous ethanol, vacuum drying to obtain the zirconium-based MOF adsorbent DKTA-MOF.

2. The method for preparing the zirconium-based MOF adsorbent according to claim 1, characterized in that: The specific steps are as follows: (1) 3-aminopyrazine-2-carboxylic acid and dibenzoylmethane are added to anhydrous ethanol solvent, stirred and dissolved to obtain solution A, acetic acid is added to solution A, and then refluxed at a temperature of 77-83°C for 7-9 hours, cooled to room temperature, separated from the solid and the liquid, and the solid is dried to obtain the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid, denoted as DKTA; (2) The ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid DKTA and ZrCl4 Ultrasonic dissolution in N,N-dimethylformamide, adding concentrated hydrochloric acid, reflux reaction at 127-133 °C for 47-49 h, cooling to room temperature, solid-liquid separation, solid washing and soaking with N,N-dimethylformamide and anhydrous ethanol, vacuum drying to obtain the zirconium-based MOF adsorbent DKTA-MOF.

3. The method for preparing the zirconium-based MOF adsorbent according to claim 2, characterized in that: In step (1), the molar ratio of 3-aminopyrazine-2-carboxylic acid to dibenzoylmethane is 1:0.4-0.

6.

4. The method for preparing the zirconium-based MOF adsorbent according to claim 2, characterized in that: The molar concentration of 3-aminopyrazine-2-carboxylic acid in solution A of step (1) is 0.002-0.003 mol / mL.

5. The method for preparing the zirconium-based MOF adsorbent according to claim 2, characterized in that: The volume ratio of acetic acid to solution A in step (1) is 1.5-2.5:

100.

6. The method for preparing the zirconium-based MOF adsorbent according to claim 2, characterized in that: Step (2) Ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid DKTA and ZrCl4 The mass ratio is 1:0.9~1.

1.

7. The method for preparing the zirconium-based MOF adsorbent according to claim 2, characterized in that: The concentration of concentrated hydrochloric acid in step (2) is 36-38 wt %, the solid-liquid ratio of the ligand dibenzoylmethane-bisaminopyrazine-2-carboxylic acid DKTA to concentrated hydrochloric acid is 1.1:0.5-0.6 g:mL, and the volume ratio of N,N-dimethylformamide to concentrated hydrochloric acid is 100:1.2-1.

45.

8. The zirconium-based MOF adsorbent according to claim 1 is used for targeted adsorption of copper ions in a solution.